2019 IEEE Radio and Wireless Symposium (RWS) 2019
DOI: 10.1109/rws.2019.8714409
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Communicating Radar using FSK and Fractional Fourier Transform for Automotive Applications

Abstract: In automotive environment, it is preferable to have a joint radar and communication system as it is able to use the same hardware and band of the spectrum for both systems. In this paper a joint radar communication system for automotive radar based on the Fractional Fourier Transform (FrFT) is presented. The performance of the system is analysed in the presence of interference arising from other users. In addition, the communication performance in terms of Bit Error Rate (BER), is analysed for different scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…When the order of the FrFT moves from 0 to 1, the energy of the low-pass signal concentrates in the middle of the pulse and very low intensity samples appear at the beginning and end of the pulse [4]. To keep the transmitted power at near consistent level and to get a continuous waveform, a threshold is applied to remove those low intensity samples.…”
Section: Waveform Designmentioning
confidence: 99%
See 3 more Smart Citations
“…When the order of the FrFT moves from 0 to 1, the energy of the low-pass signal concentrates in the middle of the pulse and very low intensity samples appear at the beginning and end of the pulse [4]. To keep the transmitted power at near consistent level and to get a continuous waveform, a threshold is applied to remove those low intensity samples.…”
Section: Waveform Designmentioning
confidence: 99%
“…The Coherent Processing Interval (CPI) of the proposed waveform design has a similar time-frequency profile with an FCFMCW signal as presented in [4] and [5]. In order to increase the Signal to Noise Ratio (SNR) and therefore improve the radar performance, the same bits of information are embedded in every waveform in a CPI, meaning that the data information change from CPI to CPI.…”
Section: Waveform Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In [4] it was shown that the radar performance of the proposed waveform design in terms of Ambiguity Function (AF) and Side Lobe Levels is similar to that of a Linear Frequency Modulation (LFM) waveform while also demonstrating that the random nature of the embedded data do not significantly impact the radar performance. Additionally, in [5] it was shown that the proposed framework can work in different communication channels while assuring a good Bit Error Rate (BER).…”
Section: Introductionmentioning
confidence: 99%